2012
DOI: 10.1111/j.1442-2018.2011.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of technology‐based care and management systems on aged care outcomes in Australia

Abstract: This study determined the impact of a computerized care documentation system on client outcomes, regulatory compliance, and staff workloads after 3 years of use. The survey was conducted at an 800-bed aged care facility, and staff using the computerized care system were invited to participate (n = 112). The survey was an adapted version of the Nurses Computer Attitudes to Technology Inventory, which was refined to make it relevant to the aged care workplace. Four multiple regression models were produced, asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…However, some perceived paper-based and electronic systems to be of similar benefit, with neither system superior in supporting communication and decision-making (Munyisia et al, 2011). This latter study also reported that initial positive perceptions of quality of information and benefits for documentation were not sustained, reinforcing the need for ongoing education and support to maintain practice change as reported by other studies in this review (McDonald and Russell, 2012; Wang et al, 2013; Zhang et al, 2012). This may be a particular problem in the aged care sector where staff turnover can be high.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…However, some perceived paper-based and electronic systems to be of similar benefit, with neither system superior in supporting communication and decision-making (Munyisia et al, 2011). This latter study also reported that initial positive perceptions of quality of information and benefits for documentation were not sustained, reinforcing the need for ongoing education and support to maintain practice change as reported by other studies in this review (McDonald and Russell, 2012; Wang et al, 2013; Zhang et al, 2012). This may be a particular problem in the aged care sector where staff turnover can be high.…”
Section: Discussionsupporting
confidence: 69%
“…Studies largely reported positive impacts for staff and care outcomes, particularly in areas of workloads, time savings, information accuracy and addressing regulatory accreditation requirements. However, successful implementation and sustainability of electronic systems required organizational commitment, resources, education, monitoring and ongoing support (McDonald and Russell, 2012; Yu et al, 2013). Barriers to successful implementation were identified as related to negative staff attitudes, and lack of familiarity with computer technology, particularly for staff with low levels of language and literacy skills (McDonald and Russell, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aged care organisations in Australia are increasingly discussing the importance of information and communication technology [ 25 ]. Much of the research effort to date has been invested in examining these technologies in residential aged care facilities [ 26 ]. Internationally, research on information and communication technology applied to gerontology is dominated by telemedicine and home monitoring techniques for the elderly, in contrast to solutions that enhance care planning, communication and information sharing among professional staff working in community aged care settings [ 27 28 ].…”
Section: Introductionmentioning
confidence: 99%